MODEL KESUKSESAN PRODUK SANITER - EMAPUTRA, ANDREAN ([Yogyakarta] : Universitas Gadjah Mada, 2015)
A company that manufactures home decorations and sanitary product had not been able to achieve the expected production utility. It was indicated by the installed production capacity (in the sink) in 2013 that had not been completely consumed. Therefore, studies that explored customer needs and their corresponding levels of customer satisfaction need to be done. Furthermore, the two main indicators of the success of these products (achieving the desired product quality and customer satisfaction) can be an entrance for achieving higher sales (long-term product success). This study was conducted in several stages with the type of product selected as the research object was the sink. First, the quality attributes of the sink on 8 dimensions of product quality (performance, aesthetics, features, conformance, reliability, durability, serviceability, and perceived quality) were identified. Second, the important level of the quality attributes were dug by questionnaires submitted to the Indonesian respondents and foreign respondents. Third, the sink quality attributes were grouped into the classification of quality attributes by the Kano model for the two groups of respondent by questionnaires. This study gave some results. First, the 90 % of the average important level of the sink quality attributes was between ‘important’ and ‘extremely important.’ Secondly, the survey that used the Kano model indicated that (1) performance was must-be quality attributes for Indonesian and foreign consumers, (2) the quality attributes of aesthetics that were not indifferent quality attributes were classified into attractive quality attributes, except excellence drainage was classified into must-be quality attributes, (3) features could improve customer satisfaction quickly through item ‘the sink price is competitive’ for both Indonesian and foreign consumers, (4) the durable sink color and scratch resistant in reliability linearly increased customer satisfaction with the fulfillment of the requirements for both the consumer groups, (5) the quality attribute ‘materials that are for maintenance are included when buying the sink’ of serviceability could increase consumer satisfaction very quickly to the both type of customers, and (6) the higher reputation of the company the higher customer satisfaction.